2001
DOI: 10.1021/la001164w
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin−Gold Colloid Conjugates:  Preparation, Characterization, and Enzymatic Activity

Abstract: Pepsin−colloidal gold conjugates were prepared by a simple protein-friendly process and the enzymatic activity of the bioconjugates is reported. The pepsin−gold conjugates are obtained by mixing colloidal gold and protein solutions at pH = 3 and, thereafter, centrifugation, washing, and redispersion of the pepsin−gold conjugate material in water. The bioconjugates in solution were characterized by UV−vis spectroscopy, fluorescence spectroscopy, and biocatalytic activity measurements while films of the bioconju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
300
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 551 publications
(326 citation statements)
references
References 39 publications
25
300
0
1
Order By: Relevance
“…when the pH is close to the pI of the protein or the nanoparticle so that the electrostatic repulsion is reduced. After adsorption, the protein can be irreversibly immobilized by those forces or a combination of them (Gole et al 2001). Potentially, the protein can get into intimate contact with the particle surface by partial or complete denaturation (Gao et al 2002), giving rise e.g.…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…when the pH is close to the pI of the protein or the nanoparticle so that the electrostatic repulsion is reduced. After adsorption, the protein can be irreversibly immobilized by those forces or a combination of them (Gole et al 2001). Potentially, the protein can get into intimate contact with the particle surface by partial or complete denaturation (Gao et al 2002), giving rise e.g.…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…The overall observation confirms the presence of protein in the samples of silver nanoparticles. It is reported earlier that proteins can bind to nanoparticles either through free amine groups or cysteine residues in the proteins (Kittel 1992;Gole et al 2001). IR spectroscopic study confirmed that the carbonyl group from amino acid residue and proteins has the strongest ability to bind metal indicating the proteins could possibly form a layer covering the metal nanoparticles (i.e., capping of AgNps) to prevent agglomeration and thereby stabilize the medium.…”
Section: Resultsmentioning
confidence: 71%
“…[28][29][30][31]. It has been proposed that free amine groups of proteins bind to AuNP resulting in its stabilization [32]. Also, cell surface bound proteins are responsible for reduction and stabilization of AuNP [31].…”
Section: Ftir Analysismentioning
confidence: 99%